La construcción de la profesionalidad docente - Oliveira de Azevedo, Heloisa Helena (Pontificia Universidad Católica del Perú. Fondo Editorial, 2013)
This article was prepared by the results of a research of a investigation about the formative strategies developed by educators related to the construction of the professionality of future childhood and elementary school teachers.From the analysis of the content of the interviews, we want to know what the educators think about the teaching profession and conducting training activities aimed at building the professionalism of future teachers.With theoretical bases for analyses related to the historical-critical conception of education, we inferred that educators have tried to break with the traditional paradigm of teacher’s education, creating new learning alternatives and stimulating the construction of a new professionality that overcomes the culture of isolated an individual thinking

El presente artículo fue construido a partir de los resultados de una investigación sobre las estrategias de formación desarrolladas por docentes vinculados a la construcción de la profesionalidad de futuros profesores de educación infantil y educación primaria. A partir del análisis del contenido de las entrevistas, se busca conocer lo que piensan los formadores acerca de la profesión docente y las acciones formativas que realizan, dirigidas a la construcción de la profesionalidad de futuros profesores. Teniendo como referencial teórico la concepción históricocrítica de la educación, se constata que los formadores han buscado romper con el paradigma tradicional de la formación docente, mediante el desarrollo de nuevas alternativas de aprendizajes y la construcción de una nueva profesionalidad que supere la cultura del aislamiento y del pensar individualizado
The construction of teaching professionality
Keywords: Teacher; Formation; Teaching Professionality; Childhood Education; Elementary School; Formación Docente; Profesionalidad Docente; Formadores; Educación Infantil; Educación Primaria; https://purl.org/pe-repo/ocde/ford#5.03.00